(untitled) (Research, Society and Development, 2021)
Introduction: the work environment is a factor that generates physical and psychological stress in a way that makes it difficult to perform one’s duties. The precariousness of the work associated with the devaluation of the nursing professional predisposes to iatrogenesis with patients, as well as the demotivation of the worker due to overload and lack of positive reinforcement contributing to the determination of better working conditions and quality of life of the worker. Objective: to identify the biopsychosocial challenges faced by the nursing team in the exercise of professional practice in view of the impacts of devaluation. Method: this is an integrative literature review study carried out in the following online databases: LILACS, BDENF e SCIELO. The sample was composed of 15 scientific articles published between 2015 and 2020. Data collection was performed during the 2nd semester of 2020, between the months of September and October, by the responsible researcher. Results: the findings of the study indicated that the deviation of attributions combined with issues of autonomy and professional identity generate feelings and experiences of devaluation and disrespect generated by attitudes of other professionals, discrimination and moral harassment from the team itself and users. The evocation of work can indicate both the condition for achieving autonomy, which emerges as the fruit of the nurse’s work, and the realization that the workload is intense in the profession. Final considerations: it is concluded that poor environmental working conditions, unhealthy conditions, low inputs, insufficient remuneration, work overload and absenteeism due to musculoskeletal diseases are the main findings that underlie these challenges within the nursing team.